Beliefs, perceptions, and treatment modalities of acne among schoolchildren in Lithuania: A cross‐sectional study. (March 2015) - Karciauskiene, Jurgita; Valiukeviciene, Skaidra; Stang, Andreas; Gollnick, Harald
Abstract Background Acne vulgaris is a chronic inflammatory disease that affects the majority of adolescents. Objectives We sought to evaluate children's and adolescents' beliefs, perceptions, sources of information, and modalities of treatment of acne. Methods A cross‐sectional study was conducted in 1277 pupils aged 7–19 years. Children and adolescents were surveyed using a self‐administered questionnaire and were subsequently examined by one specially trained dermatologist. Children and adolescents with specialist‐confirmed acne were additionally interviewed about their help‐seeking behavior and acne treatment. Results The rate of response to the study was 51.4%. The overall prevalence of acne among responders was 82.9%. According to the Leeds Revised Acne Grading System, 44.6% of responders had no acne, 49.3% had mild acne, 5.9% had moderate acne, and 0.2% had severe acne. Responders with moderate or severe acne more often knew what acne was than responders with mild acne (odds ratio [OR] 5.6, 95% confidence interval [CI] 1.3–24.3; OR 1.9, 95% CI 1.3–2.8, respectively). The three main sources of information about acne were parents (76.3%), magazines (35.5%), and friends (29.3%). The three main causal or exacerbating factors of acne pointed out by responders were poor hygiene (69.0%), hormones (65.3%), and diet (64.5%). Only 7.2% of pupils had been provided with treatment for acne by a dermatologist. The majority of pupils (84.9%) with acne had been using cosmetic remedies to control it. Conclusions Many children and adolescents consider acne to be a skin problem that is caused by lack of hygiene and misuse acne treatment modalities.